EFFECTIVENESS OF USING MULTIMEDIA SOFTWARE IN EDUCATION OF STUDENTS IN PRIMARY EDUCATION CONDITIONS - Bagbekova Laylo (Scholar Express Journal, 2024)
This article describes the approaches to the wide introduction of digital technologies into the educational process, increasing students' interest in the lesson process and flexibility through the use of multimedia software tools in primary education.
Keywords: education; information technology; modern technology